Strengthening Governmental Effectiveness Through Improved Public Administration Education And Training: The United Nations/ IASIA Task Force And The Creation Of The International Commission On Public Administration Education And Training (ICAPA) - Polya Katsamunska; Allan Rosenbaum (Transylvanian Review of Administrative Sciences, 2019)
The aim of this article is to identify and outline the relationship between governmental effectiveness and public administration education and training. The recognition of some very basic realities of the worldwide political and governmental context within which public administrators of necessity must work is highly significant for this relationship. These basic realities are revealed and discussed. The new challenges place new demands upon the institutions preparing people to manage the governments and require a renewed attention to the manner in which the next generation of public administrators will be educated and the quality of education and training provided for them. The efforts to enhance the quality of the education and training led to the establishment of the International Commission on Accreditation of Public Administration Education and Training Programs (ICAPA) by the International Association of Schools and Institutes of Administration (IASIA). The article deals with the developed eight Standards of Excellence which, on the one hand, serve as the basis for IASIA accreditation assessments and, on the other, serve to provide critically needed guidance for encouraging greater excellence in education and training activities. In this way, building of more effective government is a consequence of promoting excellence in public administration education and training.